Apple MdERF4 negatively regulates salt tolerance by inhibiting MdERF3 transcription. (November 2018) - An, Jian-Ping; Zhang, Xiao-Wei; Xu, Rui-Rui; You, Chun-Xiang; Wang, Xiao-Fei; Hao, Yu-Jin
Highlights: MdERF4 negatively regulates salt tolerance and ethylene response. MdERF4 directly binds to MdERF3 promoter and suppresses its transcription. MdERF4 is involved in ethylene-mediated salt tolerance. Abstract: Phytohormone ethylene is involved in salt stress response. As a key regulator of ethylene signaling, ethylene response factors (ERFs) have been reported to regulate salt stress tolerance. However, there are few studies on the relationship between ERFs in salt stress response. In this study, we isolated a salt-responsive gene MdERF4 . Overexpression of MdERF4 negatively regulated salt stress tolerance and ethylene response, which was contrary to that of MdERF3 transgenic lines. Biochemical assays showed that MdERF4 directly bound to the DRE motif of MdERF3 promoter and suppressed its transcription. In addition, genetic analysis revealed that MdERF4 was involved in ethylene-mediated salt tolerance. Taken together, these findings demonstrated the transcriptional regulation between MdERF4 and MdERF3 in salt stress response and provided new insight into the ethylene-modulated salt stress response.